Ответы и объяснения

2012-05-21T21:30:21+04:00

x^4-(x-12)^2=0

(x^2-x+12)*(x^2+x-12)=0

 

x^2-x+12=0                                       или x^2+x-12=0

D=1-4*(12)=-47 нет решений                    D=1-4*(-12)=49

                                                                x=(-1+7):2=3 или х=(-1-7):2=-4

 

Ответ: -4; 3.

Лучший Ответ!
2012-05-21T22:02:02+04:00

x^4-(x-12)^2=0

(x^2-x+12)*(x^2+x-12)=0

 по теореме Виета

x^2-x+12=0 

х1+х2=1

х1х2=12

х-реш.нет.

 

x^2+x-12=0

х1+х2=-1

х1х2=-12

 

х1=-4

х2=3

 

ответ:х ∈ [-4;3]